STUDI PENDAHULUAN: PENGEMBANGAN E-LKPD BERORIENTASI ESD UNTUK MENINGKATKAN LITERASI LINGKUNGAN SISWA KELAS VI SD - Nadiah Tri Rahma; Suratmi; Dwi Cahaya Nurani (Satya Widya, 2025)
This study aims to identify the needs in the development of ESD (Education for Sustainable Development) oriented E-LKPD (Electronic Learner Worksheet) to improve environmental literacy of grade VI elementary school students. The method used is descriptive qualitative as part of the 4D development model, focusing on the Define stage. Data were obtained through observations and interviews. Observations were conducted in class VI of SDN 25 Indralaya with 31 students, consisting of 21 boys and 10 girls. An interview was conducted with one sixth-grade teacher. The observation results showed limited technology facilities, such as projectors that were not optimal, as well as the lack of interactive learning media relevant to the concept of ESD. Interviews revealed that students were more enthusiastic about interesting and interactive media, while teachers indicated the need for learning media that support environmental literacy and active student involvement. The conclusion shows the need for ESD-oriented E-LKPD to increase student engagement and instill sustainability values. This media is expected to be an effective solution in supporting students' environmental literacy and ESD-based learning.